1997
DOI: 10.1183/09031936.97.10122881
|View full text |Cite
|
Sign up to set email alerts
|

Alpha1-antitrypsin phenotypes in patients with cryptogenic fibrosing alveolitis: a case-control study

Abstract: Cryptogenic fibrosing alveolitis (CFA) is an interstitial lung disease, which by definition is of unknown aetiology. Recent evidence has suggested that smoking and occupational exposure to dusts may be environmental risk factors for the disease, but there has been little research into potential host risk factors. One previous study has suggested that the prevalence of abnormal alpha1-antitrypsin phenotypes may be increased in patients with CFA. Since alpha1-antitrypsin is important in regulating inflammation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
7
0
3
Order By: Relevance
“…78 One study carried out to investigate the aetiology of rheumatoid arthritis found an unexpected association between the presence of abnormal alpha-1-antitrypsin phenotypes and CFA, 79 but this finding was not confirmed in a subsequent larger study. 80 More recently we have reported evidence of an association between CFA and proinflammatory gene polymorphisms relating to the interleukin-1 receptor antagonist and the tumour necrosis factor promoter. 81…”
Section: Genetic or Constitutional Factorsmentioning
confidence: 95%
“…78 One study carried out to investigate the aetiology of rheumatoid arthritis found an unexpected association between the presence of abnormal alpha-1-antitrypsin phenotypes and CFA, 79 but this finding was not confirmed in a subsequent larger study. 80 More recently we have reported evidence of an association between CFA and proinflammatory gene polymorphisms relating to the interleukin-1 receptor antagonist and the tumour necrosis factor promoter. 81…”
Section: Genetic or Constitutional Factorsmentioning
confidence: 95%
“…Polymorphisms of genes encoding for cytokines (interleukin [IL]-1 a, tumor necrosis factor-a, lymphotoxin a, IL-4, IL-6, IL-8, IL-10, and IL-12 [79][80][81][82][83][84][85][86][87][88]), enzymes (a 1 -antitrypsin [89,90] and angiotensinconverting enzyme [91]), profibrotic molecules (transforming growth factor-b1 [92]), coagulation pathway genes (plasminogen activator inhibitors-1 and -2), genes for surfactant protein-A and -B (70), immunomodulatory genes (complement receptor 1, NOD2/CARD15 [93]), and matrix metalloproteinase (MMP)-1 (94) have been reported to have increased frequencies in patients with sporadic IPF. Many of these have also been related to disease progression.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…The common S ( 264 Glu→Val) and Z ( 342 Glu→Lys) deficiency alleles are found in approximately 12% of the UK population3 and result in plasma α 1 -AT concentrations in the homozygote of 60% and 10%, respectively, compared with the normal M homozygote. Deficiency of α 1 -AT is associated with early onset panlobar emphysema,4 bronchiectasis,5asthma,6 and cryptogenic fibrosing alveolitis,7 although this last association was not confirmed in a subsequent study 8. Current thinking would predict that α 1 -AT deficiency in patients with cystic fibrosis would lead to a greater excess of elastase and hence more severe pulmonary disease.…”
mentioning
confidence: 98%